The Urgency Of Vision And Mission In The Development Of Integrated Independent Tourism Village In Sidomulyo Village Jember - Juhanda; Anggraini , Cristian Rizqi; Sumowo , Seno (Universitas Muhammadiyah Jember, 2023)
Vision is a value of belief in a hope, big 'dreams', and the desire of a person or group of people, and an organization to achieve set goals. The forms of policy and steps for implementing activities are established in the mission and programs. The Village Tourism Awareness Group of Sidomulyo, Jember District, has a vision and mission, policies and major program steps to lead Sidomulyo village to be independent, integrated tourism village with a global village theme based on the Indonesian nation's history: “Asia-Africa Conference”. Developing on integrated independent tourism villages in Sidomulyo is cluster-based in each Dusuns. Each cluster has its own characteristics and uniqueness in the attracting motives of its tourist sites. This big vision will lead the Sidomulyo village to be a national and global class tourist village